GFI1-Mediated Upregulation of LINC00675 as a ceRNA Restrains Hepatocellular Carcinoma Metastasis by Sponging miR-942-5p - Lu, Libai; Li, Shubo; Zhang, Ying; Luo, Zongjiang; Chen, Yichen; Ma, Jiasheng; Chen, Pengyu; Wang, Wei; Pu, Jian; Wang, Jianchu (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) remains a common malignant liver tumor across the world. Recently, increasing lncRNAs are reported in the tumorigenesis of HCC. However, the expression patterns and biological roles of lncRNAs in HCC development is poorly known. In the present research, we studied the effect of LINC00675 and found it was greatly down-regulated in HCC, which was negatively correlated with high tumor grade. LINC00675 overexpression suppressed HCC cell proliferation, cell cycle, cell migration and invasion. Meanwhile, up-regulation of LINC00675 depressed in vivo tumor growth of HCC via using a subcutaneous tumor mouse model after LINC00675 overexpression. Growth Factor Independent 1 (GFI1) is reported to be dys-regulated in multiple cancers. Interestingly, we observed that GFI1 was decreased in HCC and a positive association between them was indicated in HCC. The results revealed that GFI1 directly interacted with LINC00675 in HCC cells through carrying out RNA immunoprecipitation assay. Then, interestingly, we found GFI1 restoration significantly rescued LINC00675 knockdown triggered HCC cell proliferation, migration and invasion. To conclude, LINC00675 exerted a tumor inhibitory role in HCC via promoting GFI1 expression. These revealed a significant role of LINC00675 and GFI1 in HCC progression, which might indicate a new perspective in HCC progression and treatment.